Solar‐Driven All‐in‐One Interfacial Water Evaporator Based on Electrostatic Flocking. (13th October 2020) - Guo, Yang; Javed, Muhammad; Li, Xiaoyan; Zhai, Shixiong; Cai, Zaisheng; Xu, Bi
Abstract: Solar‐driven interfacial water evaporation is a promising strategy to produce clean water by effectively converting abundant solar energy into localized heat. However, many previously reported interfacial evaporation systems are separate and costly. In this work, an all‐in‐one interfacial water evaporator with flexibility, low‐cost, and large‐scale production based on electrostatic flocking technology is proposed. Hydrophilic microfibers (flocks) are vertically planted on the upper side of the textile substrate to enhance the light trapping for photothermal conversion and lower the latent heat for more efficient evaporation. On the other side of the textile, a highly dense and vertically aligned array of hydrophobic flocks are prepared to form a continuous air layer, reducing heat conduction from absorber to bulk water. Taking advantage of those features, the all‐in‐one evaporator achieves a good evaporation rate of 1.32 kg m −2 h −1 for pure water and 1.10 kg m −2 h −1 for seawater. Simultaneously, the evaporator demonstrates resistance to salt accumulation, resulting in its stability in brine. This all‐in‐one evaporator represents an innovative way for designing interfacial evaporators and a convenient approach to mitigate the global freshwater scarcity. Abstract : An all‐in‐one interfacial water evaporator with excellent flexibility, low cost, and good scalability based on electrostatic flocking technology, is presented. The prepared water evaporator shows good cyclic stability and long‐term durability in saline conditions with an evaporation rate of 1.32 kg m −2 h −1 and 1.10 kg m −2 h −1 for pure water and saline water, respectively.